2012
DOI: 10.3390/metabo2030567
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Cut Sets and the Use of Failure Modes in Metabolic Networks

Abstract: A minimal cut set is a minimal set of reactions whose inactivation would guarantee a failure in a certain network function or functions. Minimal cut sets (MCSs) were initially developed from the metabolic pathway analysis method (MPA) of elementary modes (EMs); they provide a way of identifying target genes for eliminating a certain objective function from a holistic perspective that takes into account the structure of the whole metabolic network. The concept of MCSs is fairly new and still being explored and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…As opposed to many of methods described previously, extreme currents aim to increase dimensionality by describing non-decomposable EFMs situated both within and on the boundaries of the flux regions; these arise as a result of partitioning each reversible reaction into two irreversible reactions [37]. Minimal cut sets (MCSs) are another variant of EFMs that result in inactivity of the system with respect to the objective reaction if removed [38]. Therefore, they can be used to identify target genes and repress undesirable metabolic functions, whilst assessing the effect on the structure of the entire metabolic network.…”
Section: Unbiased Methodsmentioning
confidence: 99%
“…As opposed to many of methods described previously, extreme currents aim to increase dimensionality by describing non-decomposable EFMs situated both within and on the boundaries of the flux regions; these arise as a result of partitioning each reversible reaction into two irreversible reactions [37]. Minimal cut sets (MCSs) are another variant of EFMs that result in inactivity of the system with respect to the objective reaction if removed [38]. Therefore, they can be used to identify target genes and repress undesirable metabolic functions, whilst assessing the effect on the structure of the entire metabolic network.…”
Section: Unbiased Methodsmentioning
confidence: 99%
“…The reliability of a system is a numerical rating of how well it is expected to perform over a certain time frame. Most tools are constructed using algorithms that are minimum path set algorithms or minimal cut set algorithms (Negi et al 2022;Clark and Verwoerd 2012). Determining network reliance via a collection of minimum pathways or cuts is NP-hard, unfortunately.…”
mentioning
confidence: 99%
“…Minimal cut sets are complementary to EMs, and consist of the minimal sets of reactions that, when blocked, will repress a certain metabolic functionality by preventing the network from achieving steady state. A review of MCSs can be found in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this idea, we can use experimental results of compounds that are found in a particular tissue, or are conversely absent, to identify the viable EMs [4] [6] [7] and MCSs [3] [5] [8] for certain tissues and, subsequently, genes that are being expressed in terms of the reactions that are taking place. This will be cheaper and easier to use than practical experimental methods such as microarrays which need advanced experimental technology to carry out and are hard to repeat.…”
Section: Introductionmentioning
confidence: 99%